PELAKSANAAN PERTOLONGAN PERTAMA KORBAN SYNCOPE PADA SISWA SMA NUR CAHAYA MEDAN - Syafrinanda, Virginia; Olivia, Nina; Lubis, Mhd. Fauzul H.; Harahap, Miranda F.Q (LPPM Institut Pendidikan Nusantara Global, 2024)
Fainting or syncope is a state of unconsciousness in a person caused by lack of blood flow to the brain, lack of oxygen, poisoning, shock, hunger, thirst and other weak physical conditions or symptoms of other chronic diseases. Fainting or syncope causes heat accompanied by dehydration, emotional stress, sudden body position such as from squatting to standing, abdominal pain, standing too long, blood loss, coughing, pain when urinating, certain medications, decreased blood sugar levels (hypoglycemia) and heart problems. The purpose of community service activities is to improve the insight of high school students by providing first aid training to syncope victims in Nur Cahaya Medan High School students. This activity will be held on August 23, 2023 with 25 high school students participating at SMA Nur Cahaya Medan. The results of community service activities found that the pretest results of the participants' knowledge level were obtained in the good category as many as 7 people (27.0%), the sufficient category as many as 10 people (38.0%), and the less category as many as 9 people (35.0%) while the posttest results of the participants' knowledge level were obtained in the good category as many as 15 people (60.0%), the sufficient category as many as 8 people (32.0%), and the less category as many as 2 people (8.0%). Based on the results of the training activities carried out, there was an increase in the level of knowledge before and after first aid training was carried out on syncope victims in Nur Cahaya Medan High School students.